2022
DOI: 10.1111/camh.12596
|View full text |Cite
|
Sign up to set email alerts
|

Preventing anxiety in the children of anxious parents – feasibility of a brief, online, group intervention for parents of one‐ to three‐year‐olds

Abstract: Background: The evidence suggests an increased risk of developing anxiety problems in children of anxious parents. The current study explored the feasibility and acceptability of an intervention with anxious parents of young children, to inform the possibility of further trials. Methods: Participants were recruited through primary and secondary care psychological services and social media. Participants who had a current or recent anxiety disorder and a child aged 12-47 months were included. Assessments of pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Each module is designed to WHY Describe any rationale, theory, or goal of the elements essential to the intervention Eligibility criteria: Parent(s) of 1) child (ren) enrolled in a mainstream primary school experiencing emotional distress associated with school attendance 2) has access to an internet-enabled device and competency in English, as required to engage with the content of the intervention Goal: To reduce EBSA through short-term outcomes of reducing parent stress, lowering children's anxiety around attending school, reducing parent accommodations and improving homeschool communication These outcomes will be achieved through: Self-care strategies to increase parent wellbeing and self-efficacy; parenting strategies to change accommodating behavioural patterns that maintain child distress and avoidance of school; and solution-focused strategies to improve home-school communication WHAT Materials: Describe any physical or informational materials used in the intervention, including those provided to participants or used in intervention delivery An online webpage with links to three modules corresponding to each topic area. Each module comprises of an interactive worksheet with four videos, reflection tasks and one home learning task Procedures: Describe each of the procedures, activities, and/or processes used in the intervention The videos aim to provide psychoeducational content on three topics known for their effectiveness in previous interventions In the first module, which focuses on managing parents' stress and wellbeing, the videos explain the significance of maintaining wellbeing, especially when caring for an anxious child (Palmer et al, 2023). They will also guide parents on recognising stress indicators and introduce specific evidence-based techniques, such as breathing exercises and muscle relaxation to alleviate stress and promote overall wellbeing (Da Paz & Wallander, 2017) In the second module, centred on the parents managing their child's anxiety, the videos address how a child's anxiety about school can contribute to an avoidance cycle (Cartwright-Hatton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Each module is designed to WHY Describe any rationale, theory, or goal of the elements essential to the intervention Eligibility criteria: Parent(s) of 1) child (ren) enrolled in a mainstream primary school experiencing emotional distress associated with school attendance 2) has access to an internet-enabled device and competency in English, as required to engage with the content of the intervention Goal: To reduce EBSA through short-term outcomes of reducing parent stress, lowering children's anxiety around attending school, reducing parent accommodations and improving homeschool communication These outcomes will be achieved through: Self-care strategies to increase parent wellbeing and self-efficacy; parenting strategies to change accommodating behavioural patterns that maintain child distress and avoidance of school; and solution-focused strategies to improve home-school communication WHAT Materials: Describe any physical or informational materials used in the intervention, including those provided to participants or used in intervention delivery An online webpage with links to three modules corresponding to each topic area. Each module comprises of an interactive worksheet with four videos, reflection tasks and one home learning task Procedures: Describe each of the procedures, activities, and/or processes used in the intervention The videos aim to provide psychoeducational content on three topics known for their effectiveness in previous interventions In the first module, which focuses on managing parents' stress and wellbeing, the videos explain the significance of maintaining wellbeing, especially when caring for an anxious child (Palmer et al, 2023). They will also guide parents on recognising stress indicators and introduce specific evidence-based techniques, such as breathing exercises and muscle relaxation to alleviate stress and promote overall wellbeing (Da Paz & Wallander, 2017) In the second module, centred on the parents managing their child's anxiety, the videos address how a child's anxiety about school can contribute to an avoidance cycle (Cartwright-Hatton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it combines components that are present within many community-delivered parenting interventions, with new components designed for a) parents who experience mental health difficulties and b) parents who specifically experience anxiety. In a randomised controlled trial (RCT), 16% fewer anxiety symptoms were reported in children whose parents were randomised to receive the course, compared to a control group ( 12 )a large (N>1800) national RCT ( 13 , 14 ) Furthermore, the research team has a track record in effectively adapting the RCC course for other contexts – it has been used by them as the foundation for an intervention designed to support NHS mental health workers who were parents ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Online therapies, including gamified, computer‐based and app‐based digital mental health interventions are also increasingly available and being shown to be as effective as face‐to‐face therapies for mild‐to‐moderate mental health problems (Hollis et al., 2017). Two new studies by Palmer, Woolgar, Carter, Cartwright‐Hatton, and Challacombe (2022) and Green et al. (2022) demonstrate the potential of parent‐mediated digital interventions for preventing and improving anxiety in their children.…”
mentioning
confidence: 99%
“…Online therapies, including gamified, computer-based and app-based digital mental health interventions are also increasingly available and being shown to be as effective as face-to-face therapies for mild-to-moderate mental health problems (Hollis et al, 2017). Two new studies by Palmer, Woolgar, Carter, Cartwright-Hatton, and Challacombe (2022) and Green et al (2022) demonstrate the potential of parentmediated digital interventions for preventing and improving anxiety in their children. These types of interventions lend themselves well to delivery in community settings, such as schools and charities or nongovernmental organisations, but we remain behind the curve on implementing such interventions at scale.…”
mentioning
confidence: 99%